General practitioners’ perceptions of COPD treatment: thematic analysis of qualitative interviews - Molin KR; Egerod I; Valentiner LS; Lange P; Langberg H (International Journal of COPD, 2016)
Katrine Rutkær Molin,1 Ingrid Egerod,2 Laura Staun Valentiner,1 Peter Lange,3 Henning Langberg1 1CopenRehab, Section of Social Medicine, Department of Public Health, University of Copenhagen, Copenhagen, Denmark; 2Department of Neuroanaesthesiology, Rigshospitalet, University of Copenhagen, Copenhagen, Denmark; 3Section of Social Medicine, Department of Public Health, University of Copenhagen, Copenhagen, Denmark Background: In Denmark, the treatment of COPD is mainly managed by general practitioners (GPs). Pulmonary rehabilitation (PR) is available to patients with COPD in the local community by GP referral, but in practice, many patients do not participate in rehabilitation. The aim of our study was to explore 1) GPs’ perceptions of their role and responsibility in the rehabilitation of patients with COPD, and 2) GPs’ perceptions of how patients manage their COPD.Methods: The study was based on a qualitative design with semi-structured key-informant interviews with GPs. Investigator triangulation was applied during data generation, and analysis was done using thematic analysis methodology.Results: Our main findings were that GPs relied on patients themselves to take the initiative to make clinic appointments and on professionals at health centers to provide the PR including consultations on lifestyle changes. The GPs experienced that patients chose to come to the clinic when they were in distress and that patients either declined or had poor adherence to rehabilitation when offered. The GPs were relieved that the health centers had taken over the responsibility of rehabilitation as GPs lacked the resources to discuss rehabilitation and follow up on individual plans.Conclusion: Our study suggested a potential self-reinforcing problem with the treatment of COPD being mainly focused on medication rather than on PR. Neither GPs nor patients used a proactive approach. Further, GPs were not fully committed to discuss non-pharmacological treatment and perceived the patients as unmotivated for PR. As such, there is a need for optimizing non-pharmacological treatment of COPD and in particular the referral process to PR. Keywords: non-pharmacological treatment, motivation theory, primary care, treatment approach, pulmonary rehabilitation, qualitative research